Penerapan Strategi Pembelajaran Aktif Tipe Giving Questions and Getting Answers untuk Meningkatkan Keaktifan Belajar Siswa pada Pelajaran Sejarah Kebudayaan Islam Kelas VII MTsS Jam’iyah Mahmudiyah Tanjung Pura - Fatimah Ahmad (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2021)
And how is the relevance of applying the active learning strategy type of giving questions and getting answers to increase student learning activeness at MTs Private Jam'iyah Mahmudiyah Tanjung Pura ?. This study aims to find an increase in understanding through the application of the strategy of giving questions and getting answers to class VII A students at MTs Jam'iyah Mahmudiyah Tanjung Pura. This research is a qualitative research which takes place at MTs Jam'iyah Mahmudiyah Tanjung Pura Langkat. Data collection methods used by documentation, observation and interviews. Meanwhile, the data analysis method used is deductive analysis, which departs from the theory and is then linked to the data in the field, if there is a continuity or relationship, and draws conclusions about which theory is most suitable in the application of the strategy of giving questions and getting answers. Based on the results of the research and data analysis, it can be concluded that the application of the strategy of giving questions and getting answers in learning Islamic Cultural History can increase the learning activity of class VII A students of MTs Jam'iyah Mahmudiyah Tanjung Pura.